Blastic plasmacytoid dendritic cell neoplasm in the background of myeloproliferative disorder and chronic lymphocytic leukaemia. Issue 7 (15th July 2019) - Khan, Abdul Moiz; Munir, Ayesha; Raval, Mihir; Mehdi, Syed
Abstract : Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is an extremely rare haematological malignancy defined by concurrent expression of CD4, CD56, BCL-2 and CD123. The disease has a very poor prognosis and there are no well-established treatment guidelines. We describe a case of BPDCN in a 65-year-old female patient with myeloproliferative disorder (essential thrombocythemia) and chronic lymphocytic leukaemia. She presented with rapidly progressive facial and scalp lesions. Skin biopsy confirmed BPDCN and the imaging revealed widespread disease. Patient was started on hyper-CVAD (cyclophosphamide, vincristine, doxorubicin, dexamethasone) and intrathecal methotrexate. Due to progression on initial treatment, she was treated with decitabine and venetoclax (BCL-2 inhibitor). However, patient continued to deteriorate and died after 4 months from initial diagnosis. We emphasise on the clinical features, emerging treatment modalities and prognosis of BPDCN.